Neurospora perithecia: The first sighting - D D Perkins (Fungal Genetics Reports, 2002)
When Shear and Dodge (1927) observed perithecia in laboratory cultures of Monilia sitophila, they concluded on the basis of ascospore ornamentation that the fungus merited diagnosis as a new genus, Neurospora. Prior to this, there had been reports of perithecia and ascospores formed in nature by orange fungi that must have been Neurospora. Neurospora perithecia were not found again in nature until 1996.